How Effective Is Blended Learning for Short Courses In Language and Art for International Students? - Arnailis Arnailis; Nurmalena Nurmalena; Awerman Awerman; Murniati Murniati; Firdaus Firdaus; Hasnah Hasnah (Aksara, 2023)
The objective of this study is to investigate the progress and ability of English for international students who are less fluent when they learn English to make it easier to understand art learning materials that are compatible with media understanding during face-to-face or online learning. This research was conducted on international students of the Indonesian Institute of Arts Padangpanjang during the pandemic. Data collection is carried out using distribution methods using listening techniques and analysis of results with average calculations. The findings of this study show that international students with lower levels of English proficiency who receive instruction through online learning platforms show better learning outcomes than their peers who receive instruction through offline means. This conclusion is reached through hypothesis testing. The use of online learning media for teaching groups of students who have open interpersonal communication, results in better English learning outcomes for that group of students than the use of offline learning media for the same group of students.AbstrakTujuan dari penelitian ini adalah untuk menyelidiki kemajuan dan kemampuan bahasa Inggris bagi siswa internasional yang kurang lancar ketika mereka belajar bahasa Inggris agar lebih mudah memahami materi pembelajaran seni yang sesuai dengan pemahaman media selama pembelajaran tatap muka atau online.. Penelitian ini dilakukan pada mahasiswa internasional Institut Seni Indonesia Padangpanjang di masa pandemi. Pengumpulan data dilakukan dengan menggunakan metode distribusi dengan menggunakan teknik menyimak dan analsis hasil dengan perhitungan rata-rata. Temuan penelitian ini menunjukkan bahwa siswa internasional dengan tingkat kecakapan bahasa Inggris yang lebih rendah yang menerima pengajaran melalui platform pembelajaran online menunjukkan hasil belajar yang lebih baik dibandingkan rekan mereka yang menerima pengajaran melalui cara offline. Kesimpulan ini dicapai melalui pengujian hipotesis. Penggunaan media pembelajaran online untuk pengajaran kelompok siswa yang memiliki komunikasi interpersonal terbuka, menghasilkan hasil belajar bahasa Inggris yang lebih baik untuk kelompok siswa tersebut daripada penggunaan media pembelajaran offline untuk kelompok siswa yang sama.